Selective Oxidation of Methionine and Tryptophan Residues in a Therapeutic IgG1 Molecule. Issue 9 (25th May 2015) - Folzer, Emilien; Diepold, Katharina; Bomans, Katrin; Finkler, Christof; Schmidt, Roland; Bulau, Patrick; Huwyler, JÖRg; Mahler, Hanns‐Christian; Koulov, Atanas V.; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; et al.
<x xml:space="preserve">Abstract</x> Oxidation of methionine and tryptophan are common degradation pathways for monoclonal antibodies and present major analytical challenges in biotechnology. Generally, protein oxidation is detectable in stability and/or stressed samples (e.g., exposed to hydrogen peroxide, UV light, or metal ions). The induced chemical modifications may impact the biological activity of antibodies and may have biological consequences. However, these effects and the contribution of individual protein modifications are difficult to delineate as different amino acids are often oxidized simultaneously and accompanied by other degradants such as aggregates, especially in forced degradation studies. Here, we report a new method to obtain selective oxidation of methionine or tryptophan by using oxidation reagents combined with large excess of free tryptophan or methionine, correspondingly. More specifically, using hydrogen peroxide or tert‐butyl hydroperoxide in combination with addition of free tryptophan allowed for selective oxidation of methionine. Conversely, the use of 2, 2‐azobis(2‐amidinopropane) dihydrochloride in combination with free methionine resulted in selective tryptophan oxidation, whereas methionine oxidation was not significantly altered. This novel stress model system may prove to be valuable tool in future mechanistic studies of oxidative degradation of protein therapeutics. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2824–2831, 2015